STUDY OF THE REVERSE CURRENT OF A PHOTODIODE FOR THE GENERATION OF A RELIABLE RANDOM SEQUENCE OF NUMBERS - DOBROVOLSKY, YURIY; DYACHUK, ROSTISLAV (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The paper presents the results of research in the direction of creating reliable, secure cybersecurity protocols based on the generation of externally unpredictable pseudo-random, chaotic numerical sequences. Methods for generating random sequences are, in turn, one of the defining components of cybersecurity from the point of view of software engineering, namely, ensuring the security of incoming and outgoing data flows. The source of entropy (chaos) can be used to generate random numerical sequences. This provides a certain uniqueness and, most importantly, unpredictability of values. Such pseudo-random numerical sequences are used in various networks to ensure efficient and secure connections, generate cryptographic keys, monitor integrity, and in many other areas. The purpose of our research was to examine the question of whether it is possible to use the value of the reverse current, for example, of a darkened photodiode, as a source of a random numerical sequence. The interest in this issue is due to the fact that the reverse current of a photodiode operating in the photodiode mode, i.e. when electrically biased at the p-n junction, is a truly physically unpredictable quantity. As a result of the study, it turned out that if the reverse (otherwise - dark) current of the photodiode is used as a source of a random sequence, the random number generation performance for Arduino will be 980 bytes/sec., which is quite small, since the histogram of the distribution of the value of random numbers, obtained by methods using the DescriptiveStatistics library, is close to the Gaussian distribution. But, if you amplify the dark current signal to 5 Volts, the histogram of the distribution of the value of random numbers obtained from the FD using an amplifier is uniformly chaotic. Namely, each number is represented approximately evenly in the range of 0.3 - 0.7%. Given that the ideal fraction for each number in this case (1/256) is 0.4%. Thus, it is shown that the photodiode, namely its reverse (dark) current, can be a source of entropy for generating random numbers.
Keywords: Software engineering; cybersecurity; photodiode; dark current; random numbers